THE VANNAMEI PRAWNS AQUACULTURE BASED COASTAL CARRYING CAPACITY IN THE COAST AREAS OF INDRAMAYU - Wigiani, Dwi Putri; Widigdo, Bambang; Soewardi, Kadarwan; Taryono, Taryono; Rahmadya, Aldiano (Indonesian Aquaculture Society (MAI), 2019)
The utilization of coastal area nowadays is commonly used for vannamei prawns aquaculture, either with traditional technology ?plus? and intensive technology. The regency of Indramayu is a district in which coastal regions are now utilized to vannamei prawns aquaculture. The uncontrolled development of this aquaculture farming will cause an impact on the surrounding environment, and will eventually threaten other environment sectors in the coastal areas of Indramayu. This research was aimed to calculate the carrying capacity of Indramayu sub-district coastal area. The results of the measurement of the coastal area in Indramayu showed that the aquaculture activities were not exceeding its carrying capacity. It is demonstrated by the high productivity of biomass, which is 21 000 tons of vannamei prawn per year from the ideal productivity of only 1959 tons per year. This condition could be occurred due to the water quality in the coastal of Indramayu is still relatively good with the quality status of mild pollutants.